Current status of pharmacotherapy for primary sclerosing cholangitis - Hang Yang; Juan Zhen; Xiaoyan Huang; Minqi Chen; Hongsi Cui; Xia Sheng; Xinyu Li (Frontiers in Medicine)
Primary sclerosing cholangitis (PSC) represents a cholestatic disease hallmarked by persistent and progressive inflammation of the bile ducts. Despite its low incidence and unfavorable prognosis, there is no pharmacological therapy capable of altering the course of PSC, and liver transplantation is the only effective treatment. In the face of the landscape of PSC, pharmaceutical therapy encounters great challenges that demand expeditious resolution. However, at present, many drugs have been carried out to phase III clinical trials and are expected to be applied to the clinical treatment of PSC patients in the future. This review integrates relevant research findings from PubMed and Web of Science databases up to October 2024 over the past decade, excluding other liver diseases, such as fatty liver disease, viral hepatitis, and alcoholic liver disease. It covers the vast majority of drugs currently in clinical trials, and focus on the summary of hot research drugs, and summarizes the latest drug-based therapeutic for PSC. This review not only provides certain information for clinical research and treatment of PSC, but it is also the first time that stem cell therapy has been linked to PSC, which is expected to improve cholestasis and liver inflammation in patients with PSC. The article provides explanations and comparisons of different drugs, offering a basis for future researchers to choose medications.